Συγκριτική ανάλυση της διαφθοράς και της ανάπτυξης επιχειρήσεων στη Νότια Ευρώπη, την Ανατολική Ευρώπη και τη Κεντρική Ασία - Αθανασούλη, Δάφνη (Πανεπιστήμιο Πελοποννήσου, 2016)
Corruption has been on the focus of research and policy making in recent years. This thesis "Comparative Analysis of Corruption and Business Growth in South Europe, Eastern Europe, and Central Asia" extends the research on corruption and evaluates in detail its impact on business growth. This thesis is innovative in five main aspects. It analyses the corruption phenomenon in light of International Political Economy. It adopts and interdisciplinary approach. It focuses on Southern Europe, Eastern Europe and Central Asia, and provides case studies on Greece. It examines the heterogeneous impact of corruption on firms, based on different measures of corruption. It is based both on well-known datasets and primary data. The first introductory chapter offers a new analytical framework for the analysis of corruption and its determinants. A plethora of studies have contributed effectively to the existing knowledge and understanding of the phenomenon of corruption and its determinants. The chapter produces a new categorization of the determinants of corruption, the dynamic links between them and their evolving process. The second chapter investigates the relationship between corruption and firm performance using firm level data in South Europe, Eastern Europe, and Central Asia. It distinguishes between “administrative corruption”, and “state capture”, to evaluate the effect of corruption on businesses. At the individual firm level, corruption is not found to be negative for firm size. However, at the regional and country level, I find that firms do not internalize the aggregate costs of corruption, which remain negative and significant for all firms. The study disentangles the impact of corruption on the firm, sector, regional, and country level, and offers a new insight on the contextual effect of corruption. The third chapter investigates the relationship between corruption and firm performance in Greece using firm level data. The analysis of the effect of corruption on business growth has not been conducted for Greece and with this level of precision. It is particularly interesting to have access and gain insight to these data for approximately 550 Greek firms to be able to draw conclusions at the regional and sectoral level. Chapter four analyses new face-to-face interviews with businesses in Greece to provide a more precise picture of the business barriers they are facing. The collection of primary data through face-to-face interviews allows to acquire new and in-depth qualitative and quantitative information on business conditions in Greece and to identify more precisely possible policy reforms. The thesis concludes on chapter five by examining the relationship between institutions and corruption to form the base of a business development model framework for firms and the institutions that affect them under a corrupt business environment. Although corruption has been shown to harm the business environment and specific types of companies more than others, the level of corruption and the degree it hampers various companies depends on institutions and the legislative framework in force in each country on the establishment, operation and business development.
A comparative analysis of corruption and business growth in South Europe, Eastern Europe and Central Asia
Keywords: Διαφθορά--Ευρώπη, Νότια; Διαφθορά--Ευρώπη, Ανατολική; Διαφθορά--Ασία, Κεντρική; Οικονομική ανάπτυξη; Επιχειρήσεις; Διαφθορά; Επιχειρηματικότητα; Νότια Ευρώπη; Ανατολική Ευρώπη; Κεντρική Ασία